2022
DOI: 10.1108/jocm-06-2021-0185
|View full text |Cite
|
Sign up to set email alerts
|

How do firms upgrade innovation capabilities through the coevolution of post-merger integration and network reconstruction? A multiple-case study of Chinese companies

Abstract: Purpose Post-merger integration (PMI) is driven by coevolving processes. This paper examines the coevolution of dynamic integration strategy and network reconstruction and explores how these processes systematically enable emerging market acquirers to upgrade innovation capabilities.Design/methodology/approach This paper conducts a multi-case study based on four Chinese overseas acquisitions of manufacturing firms. The data were collected from interviews and archival documentation.Findings This study develops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…In particular, it can be seen from the measurement model that if research actors can well define each step of innovation process (PI2) and able to commercialize the innovations (PI6), then these can lead to the emergence of solid competencies to smoothen the innovation process during organizational change due to merger. Several past studies revealed that to meet organizational goals during merger, main actors of R&D should be able to take agile actions, especially in knowledge spill-over and prompt commercialization (Bolívar-Ramos et al, 2012;Chen et al, 2022;Fernandez et al, 2018b;Real et al, 2006;Taghizadeh et al, 2020;van Lieshout et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it can be seen from the measurement model that if research actors can well define each step of innovation process (PI2) and able to commercialize the innovations (PI6), then these can lead to the emergence of solid competencies to smoothen the innovation process during organizational change due to merger. Several past studies revealed that to meet organizational goals during merger, main actors of R&D should be able to take agile actions, especially in knowledge spill-over and prompt commercialization (Bolívar-Ramos et al, 2012;Chen et al, 2022;Fernandez et al, 2018b;Real et al, 2006;Taghizadeh et al, 2020;van Lieshout et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…But, as our case study shows, during the re-noding, not only the new counterparts, but also the prior counterparts bring new knowledge to the business network that is developed. Although previous studies have shown that network reconstruction promotes the upgrading of innovation capabilities (Chen, Wang, & Zhu, 2022), the aspects of re-noding and its consequences for network reconstruction when resuming business operations represent an area of research that fills a void in the existing business network dynamics literature.…”
Section: Re-noding In Business Networkmentioning
confidence: 99%